The Effect of Operational Efficiency, Investment Decisions, and Capital Structure on Financial Performance in Conventional State-Owned Banking Companies Listed on the Indonesia Stock Exchange - Nabila Fahira; Yancik Syafitri; Dwi Septa Aryani (International Journal of Business and Quality Research, 2026)
This study aims to analyze the influence of operational efficiency, investment decisions, and capital structure on financial performance of conventional state-owned banking companies listed on the Indonesia Stock Exchange during the period 2016–2025. The research sample consisted of 4 companies with a total of 40 annual financial statement observations. The data analysis method used was multiple linear regression analysis with the assistance of SPSS software version 25.0. The results of the study indicate that operational efficiency, investment decisions, and capital structure simultaneously have a significant effect on financial performance, as evidenced by an F-value of 35.798 with a significance level of 0.001 (sig. < 0.05). Partially, operational efficiency, measured by the Operating Expenses to Operating Income ratio, has a significant effect on financial performance with a t-value of -5.077 and a significance level of 0.001. Investment decisions, measured by Total Asset Growth, have a significant effect on financial performance with a t-value of -2.391 and a significance level of 0.022. Furthermore, capital structure, measured by the Debt to Equity Ratio, has a significant effect on financial performance with a t-value of -2.815 and a significance level of 0.008.